2011
DOI: 10.1080/01635581.2011.570892
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 Fatty Acid Inhibition of Prostate Cancer Progression to Hormone Independence Is Associated With Suppression of mTOR Signaling and Androgen Receptor Expression

Abstract: Currently, progression of prostate cancer to androgen independence remains the primary obstacle to improved survival. In order to improve overall survival, novel treatment strategies that are based upon specific molecular mechanisms that prolong the androgen-dependent state and that are useful for androgen-independent disease need to be identified. Both epidemiological as well as preclinical data suggest that omega-3 fatty acids are effective primary tumor prevention agents; however, their efficacy at preventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 30 publications
4
49
0
Order By: Relevance
“…An increase in dietary ω-3 fatty acids has been linked to good prostate health (3,32) and prevention of prostate cancer progression to androgen independence (33). In general, there is good concurrence that fish oil is beneficial in reducing the risk of prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…An increase in dietary ω-3 fatty acids has been linked to good prostate health (3,32) and prevention of prostate cancer progression to androgen independence (33). In general, there is good concurrence that fish oil is beneficial in reducing the risk of prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Among the various dietary products that have been implicated in promoting health are the dietary omega-3 and omega-6 polyunsaturated fatty acids (ω3PUFAs/ω6PUFAs). ω3PUFAs have been shown to contribute to the prevention of many cancers, including breast, prostate, and colon cancers; 9,10 however, the anti-tumorigenic activity of ω3PUFAs is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…A combination of indol-3-carbinol and genistein synergistically induces apoptosis and autophagy in human colon cancer HT-29 cells by inhibiting Akt phosphorylation [37]. Friedrichs et al indicated that polyunsaturated fatty acids can prevent the progression of prostate cancer cells to hormone independence by modifying signal transduction pathways such as the Akt/mTOR pathway [28]. An intact PI3K/Akt pathway is required for LNCaP cells to progress to hormonerefractory state, and Akt activity increases as the cells transform from hormone-dependent to hormone-independent [6].…”
Section: Discussionmentioning
confidence: 99%